Investigation of Microstructure and Magnetic Properties of Zn1-xMnxO and Zn0.98-xMnxFe0.02O (x = 0, 0.05, and 0.09) prepared by Solid-state Reaction Method - Sebayang, Perdamean; Kurniawan, Candra; Lubis, Ridwan Y; Priyadi, Ignu; N, Nasruddin M; Aryanto, Didik (UI Scholars Hub, 2020)
In this study, we investigated the microstructure and magnetic properties of Zn1-xMnxO and Zn0.98-xMnxFe0.02O (x = 0, 0.05, and 0.09) powders prepared by the solid-state reaction method. The starting material, which consisted of ZnO, Mn, and Fe powders, were wet milled for 3 hours using high-energy milling. We then used an X-ray diffractometer (XRD), scanning electron microscope, and vibrating sample magnetometer to investigate the effects of doping and co-doping on the microstructure, morphology, and magnetic properties, respectively. The XRD results suggest that Mn and Fe ions had substituted into the ZnO matrix, as illustrated by the resulting single-phase polycrystalline hexagonal wurtzite structures. The diffraction intensity was observed to decrease as the Mn composition increased. The analysis showed that the lattice parameters decreased due to Mn2+ and Fe3+ ion substitution in the ZnO matrix. The co-doping of Mn-Fe ions in the ZnO structure enhanced the magnetic properties, particularly due to the Zn0.89Mn0.09Fe0.02O composition. The increase in the Mn dopant and Mn-Fe co-dopant concentrations strongly contributed to the improved morphology and magnetic properties. Therefore, we can conclude that the presence of Mn and Fe co-dopants in the ZnO system contributed to its magnetic properties, as confirmed by high-saturation magnetization.